Regulating Immunity via ADP-Ribosylation: Therapeutic Implications and Beyond. Issue 2 (February 2019) - Kunze, Friedrich A.; Hottiger, Michael O.
Abstract : Innate immune cells express pattern recognition receptors (PRRs) that recognize pathogen-associated molecular patterns (PAMPs) and endogenous danger-associated molecular patterns (DAMPs). Upon binding, PAMPs/DAMPs can initiate an immune response by activating lymphocytes, amplifying and modulating signaling cascades, and inducing appropriate effector responses. Protein ADP-ribosylation can regulate cell death, the release of DAMPs, as well as inflammatory cytokine expression. Inhibitors of ADP-ribosylation (i.e. PARP inhibitors) have been developed as therapeutic agents (in cancer), and are also able to dampen inflammation. We summarize here our most recent understanding of how ADP-ribosylation can regulate the different phases of an immune response. Moreover, we examine the potential clinical translation of pharmacological ADP-ribosylation inhibitors as putative treatment strategies for various inflammation-associated diseases (e.g. sepsis, chronic inflammatory diseases, and reperfusion injury). Highlights: ADP-ribosylation serves as a checkpoint control for cell fate and actively drives a type of regulated cell death (parthanatos) to induce inflammation. ARTD1-mediated poly-ADP-ribosylation affects the mRNA stability of proinflammatory cytokines. The ARTD9–DTX3L complex acts as a potent antiviral mediator via chromatin modification and viral protein degradation. ARTD8 and ARTD9 regulate macrophage polarization via STAT1 phosphorylation and ADP-ribosylation. ARTD10-mediated mono-ADP-ribosylation of NEMO inhibits its degradation, consequently dampening NF-κB gene expression. Ectopic ARTC2.1 on microglia can regulate phagocytosis by modifying immunoglobulin receptors.